2000
DOI: 10.1677/joe.0.1650359
|View full text |Cite
|
Sign up to set email alerts
|

Localization of oestrogen receptor alpha, oestrogen receptor beta and androgen receptors in the rat reproductive organs

Abstract: There is now evidence that oestrogens and androgens can influence male and female reproductive systems. In order to accurately identify the sites of action of oestrogens and androgens, we have proceeded to the histological localization of the two oestrogen receptor (ER) subtypes, ER and ER , and the androgen receptor (AR) in the reproductive tissues of adult rats of both sexes. AR was detected by immunocytochemistry, while ER and ER were localized by both immunocytochemistry and in situ hybridization. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
236
2
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(267 citation statements)
references
References 40 publications
25
236
2
4
Order By: Relevance
“…Testosterone withdrawal decreased endothelial cell proliferation, showing that hormonally regulated endothelial cell proliferation is not unique to female reproductive tract but takes place also in male reproductive organs (Lissbrant et al 2003). Besides, androgen receptors have been shown in endothelial cells in rat and human prostate (El Alfy et al 1999, Pelletier et al 2000. The high proliferation rate in endothelial cells suggests remodeling of the testicular microvasculature (Collin & Bergh 1996), which might have occurred in the testes of the most food-restricted rabbits (group C), in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…Testosterone withdrawal decreased endothelial cell proliferation, showing that hormonally regulated endothelial cell proliferation is not unique to female reproductive tract but takes place also in male reproductive organs (Lissbrant et al 2003). Besides, androgen receptors have been shown in endothelial cells in rat and human prostate (El Alfy et al 1999, Pelletier et al 2000. The high proliferation rate in endothelial cells suggests remodeling of the testicular microvasculature (Collin & Bergh 1996), which might have occurred in the testes of the most food-restricted rabbits (group C), in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…However, little is known about their effects on sexual hormone receptors (ERa, ERJ3 and AR) in testis. ERa is localized in nuclei of Leydig cells, round spermatocytes and spermatids in the testis, and ERJS is found in Sertoli cell nuclei, and AR is localized in nuclei of Sertoli cells, peritubular myoid cells and Leydig cells during prepubertal development [18,19]. A recent study has demonstrated that ERa knockout mice show male infertility in adulthood [20].…”
mentioning
confidence: 99%
“…Excluding some splicing variants, two major estrogen receptor (ER) forms, namely ERα and ERβ are expressed in both the epithelial and stromal cells of the rodent uterus [21][22][23][24][25][26][27]. Although ERβ is detected to a lower level and exclusively in the late phase of gestation, both forms are expressed throughout gestational development in a temporalspecific manner [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although ERβ is detected to a lower level and exclusively in the late phase of gestation, both forms are expressed throughout gestational development in a temporalspecific manner [5]. As for the androgen receptor (AR) it is expressed in both types of epithelial cells (glandular and luminal), in stromal and smooth muscle cells of the rat and mouse [27][28][29], and in the human uterus [30].…”
Section: Introductionmentioning
confidence: 99%